2009
DOI: 10.1073/pnas.0905918106
|View full text |Cite
|
Sign up to set email alerts
|

Costly punishment does not always increase cooperation

Abstract: In a pairwise interaction, an individual who uses costly punishment must pay a cost in order that the opponent incurs a cost. It has been argued that individuals will behave more cooperatively if they know that their opponent has the option of using costly punishment. We examined this hypothesis by conducting two repeated two-player Prisoner's Dilemma experiments, that differed in their payoffs associated to cooperation, with university students from Beijing as participants. In these experiments, the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
123
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(134 citation statements)
references
References 20 publications
(33 reference statements)
7
123
2
2
Order By: Relevance
“…Rewarding and punishing human behavior has also been tested by using sequential PD games (often called gift exchange or trust games) [43]. In other cases, the payoff matrix of the PD game has been modified in order to include three types of players: cooperators, defectors, and punishers [44]. Moreover, the use of pairwise interactions is also present in models with incentive strategies [36].…”
Section: R S T P mentioning
confidence: 99%
“…Rewarding and punishing human behavior has also been tested by using sequential PD games (often called gift exchange or trust games) [43]. In other cases, the payoff matrix of the PD game has been modified in order to include three types of players: cooperators, defectors, and punishers [44]. Moreover, the use of pairwise interactions is also present in models with incentive strategies [36].…”
Section: R S T P mentioning
confidence: 99%
“…Punishment can increase cooperation levels if there are opportunities to punish defectors, that is, decreasing a defector's immediate payoff at a personal immediate cost (Fehr & Gächter, 2002;Raihani et al, 2010;Raihani et al, 2012;Sigmund, 2007). Until recently, such costly punishment has been perceived as an evolutionary puzzle because punishers accept costs to harm others while third parties benefit from the increased cooperation levels (Dreber et al, 2008;Fehr & Gächter, 2002;Rankin et al, 2009;Sigmund, 2007;Wu et al, 2009). However, if punishers can build up a punishment reputation that affects later decisions of others, punishment can lead to long-term benefits that compensate or even outweigh the immediate costs of punishment (dos Santos et al, 2011;dos Santos et al, 2013;Hilbe & Sigmund, 2010;Hilbe & Traulsen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency ratio of punishment is then ␣:␤ ϭ 2:3 which is far less conducive to punishment than the ␣:␤ ϭ 1:4 punishment ratio assumed by the authors (3,4). A further problem with the experimental set-up is that players can only choose between cooperating, defecting, or punishing.…”
mentioning
confidence: 97%
“…In conclusion, the game settings that have been used in recent studies (3,4) on the evolutionary significance of costly punishment are problematic. It can therefore not yet be concluded that costly punishment is unlikely to evolve to increase cooperation.…”
mentioning
confidence: 99%
See 1 more Smart Citation